Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3389/fnhum.2010.00167
|View full text |Cite
|
Sign up to set email alerts
|

Reducing barriers to ethics in neuroscience

Abstract: Ethics is a growing interest for neuroscientists, but rather than signifying a commitment to the protection of human subjects, care of animals, and public understanding to which the professional community is engaged in a fundamental way, interest has been consumed by administrative overhead and the mission creep of institutional ethics reviews. Faculty, trainees, and staff (n = 605) in North America whose work involves brain imaging and brain stimulation completed an online survey about ethics in their researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
3
15
0
1
Order By: Relevance
“…Data from that study and others suggest that researchers see ethics as complex, overregulated, and overly time consuming [15,16]. However, considerable differences also exist between our neurodegeneration research study and the neuroimaging study.…”
Section: Discussionmentioning
confidence: 90%
“…Data from that study and others suggest that researchers see ethics as complex, overregulated, and overly time consuming [15,16]. However, considerable differences also exist between our neurodegeneration research study and the neuroimaging study.…”
Section: Discussionmentioning
confidence: 90%
“…However, it must be acknowledged that the effectiveness of such committee ethics has been questioned on a number of grounds. The general barriers to the debate and implementation of best practice include lack of resources and administrative burden (Illes et al 2010). Additionally, researchers actively engaged in animal research, and others who may be seen to have a vested interest in animal research, have been suggested to be over-represented on such committees in the USA (Hansen 2013).…”
Section: Rules and Recommendations: The Need For Flexibilitymentioning
confidence: 99%
“…In other words, a precondition for making business studies a science as well as a consequence of the resulting belief in determinism has been the explicit denial of any role of moral or ethical considerations in the practice of management. (Ghoshal, 2005, p. 79) Neuroethicists have already identified that ethics training for researchers involved in this type of research is a matter of priority (Illes et al, 2010), a notion others also extend to teaching these issues on MBA programs (Morein-Zamir & Sahakian, 2009). The framework for research ethics (FRE) issued by the U.K. Economic and Social Research Council (ESRC, 2010) may be a helpful starting point to consult for those responsible for doctoral training or those involved in leadership development programs, as it delineates research projects of a less risky nature in terms of ethical ramifications from those that are considered carrying more than minimal risks.…”
Section: Future Of Neuroscience In Leadership Researchmentioning
confidence: 99%